Application of fucoidan as treatment for cardiovascular and cerebrovascular diseases. (February 2022) - Wang, Ke; Xu, Xueli; Wei, Qiang; Yang, Qiong; Zhao, Jiarui; Wang, Yuan; Li, Xia; Ji, Kai; Song, Shuliang
Fucoidan is a marine polysaccharide. In recent years, fucoidan has attracted wide-scale attention from the pharmaceutical industries due to its diverse biological activities such as lipid-lowering, anti-atherosclerosis, and anticoagulation. This review clarifies the pharmacological effects of fucoidan in the treatment of human cardiovascular and cerebrovascular diseases. Fucoidan exerts a hypolipidemic effect by increasing the reverse transport of cholesterol, inhibiting lipid synthesis, reducing lipid accumulation, and increasing lipid metabolism. Inflammation, anti-oxidation, and so on have a regulatory effect in the process of atherosclerosis endothelial cells, macrophages, smooth muscle cells, and so on; fucoidan can not only prevent thrombosis through anticoagulation and regulate platelet activation, but also promote the dissolution of formed thrombi. Fucoidan has a neuroprotective effect, and also has a positive effect on the prognosis of the cardiovascular and cerebrovascular. The prospects of applying fucoidan in cardio-cerebrovascular diseases are reviewed to provide some theoretical bases and inspirations for its full-scale development and utilization.